(untitled) (Journal of the College of Basic Education, 2022)
Music and singing accompanied theatrical performances for children as an important audio medium and an effective element in the interpretation of events and variables of expression and dramatic values through which attraction and suspense were achieved, so the need for the role of music and singing in children’s theatre performances emerged, and the importance of research: it benefits college and college students, researchers, children’s theatre workers, and teachers of artistic education in riamen kindergarten children and elementary schools . The aim of the research was: to learn about how to employ songs and music and their role in the performances of the children’s theater, this in (chapter one), and the second chapter (theoretical framework) included two topics, the first research: addressing a historical overview of the song and music and the theater of the child, but the second topic: the importance of music, singing and sound effects in the performances of the child theater, and was one of the most important indicators of the theoretical framework, that music and singing in the children’s theater is important in being the march of the life of the child and the development of his educational idea in different values in building his personality and taste Aesthetic and intellectual sense, and included (chapter three) research procedures, where the researcher analyzed the sample of research, used the analytical descriptive approach in dealing with the research community in the analysis of a theatrical presentation of children (eight days a week) sample of his research in which he dealt with the story of the play, and included (chapter four) the results of the research and discussion, the most important of which was: music and singing beside sound effects in the performances of the theater of the child puts the recipient (child) inside the dream fantasia achieved in the conflict of dramatic events when the music possesses pleasure and imagination And an important role in the performances of the children’s theater, which contribute to its creation, education, as well as entertainment, the researcher recommended the need to enhance the place of the theater for audio elements besides visual in providing what is better in the light of modernity and beyond, and conclude the research with accessories, sources and references, as well as summary of research in English